2019
DOI: 10.1111/ggi.13694
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and incident dementia in older Japanese adults: The Okayama Study

Abstract: Aim To evaluate the association between the amount and frequency of alcohol consumption and incident dementia in older Japanese adults using large sample size data over a long follow‐up period. Methods This was a retrospective cohort study carried out in Japan. A total of 53 311 older adults were followed from 2008 to 2014. A health checkup questionnaire was used to assess the amount and frequency of alcohol consumption. The Dementia Scale of long‐term care insurance was used as a measure of incident dementia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In four studies, a standard drink or unit was defined as 13 and 15 grams of alcohol, respectively, while six studies defined a standard drink or unit as 14 grams of alcohol. Studies conducted in China [ 109 ] and Japan [ 59 , 70 , 111 ] defined a standard drink of unit as 50 grams of alcohol [ 109 ] and 20–23 grams of alcohol [ 59 , 70 , 111 ], respectively. Three studies used several definitions of one standard drink [ 59 , 99 , 118 ], whereas two studies defined the alcohol content in one drink in ounces [ 60 , 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…In four studies, a standard drink or unit was defined as 13 and 15 grams of alcohol, respectively, while six studies defined a standard drink or unit as 14 grams of alcohol. Studies conducted in China [ 109 ] and Japan [ 59 , 70 , 111 ] defined a standard drink of unit as 50 grams of alcohol [ 109 ] and 20–23 grams of alcohol [ 59 , 70 , 111 ], respectively. Three studies used several definitions of one standard drink [ 59 , 99 , 118 ], whereas two studies defined the alcohol content in one drink in ounces [ 60 , 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…The components were non-smoking and moderate drinking. In a sevenyear cohort study by Liu et al [33], the non-drinkers showed a .79-and .87-times lower risk of dementia for men and women, respectively, compared to individuals who drank daily. Drinking more than one drink per day would increase the risk of dementia.…”
Section: Discussionmentioning
confidence: 96%
“…One study reported that alcohol consumption of ≤2 units/day (one unit is defined as a beverage containing approximately 20 g alcohol) could reduce the risk of dementia among older Japanese adults. 34 However, a previous review reported a dose-response effect of alcohol consumption on the deterioration of cognitive function. Frequent heavy alcohol consumption may damage brain function and decrease cognitive functions, whereas light to moderate alcohol consumption has protective effects.…”
Section: Discussionmentioning
confidence: 99%